Crystal structure and magnetic properties of TmV0.17Ge2 and LuV0.15Ge2 ternary germanides. (February 2020) - Konyk, M.; Baran, S.; Romaka, L.; Szytula, A.; Romaka, V.V.
Abstract: In this study, the new germanides TmV0.17 Ge2 and LuV0.15 Ge2 were synthesized from elements by arc-melting, before annealing at 870 K, and investigating using powder X-ray diffractometry and energy-dispersive X-ray spectroscopy analysis. The new ternary phases crystallized in the CeNiSi2 structure type (space group Cmcm ) and they were characterized by the partial occupation of one of the 4 c sites by vanadium atoms. The magnetic properties were measured in the temperature range from 1.9 to 390 K. The magnetic susceptibility of TmV0.17 Ge2 obeys the Curie–Weiss law in the paramagnetic region at high temperatures, whereas the low temperature data indicated cluster-glass behavior. Almost temperature-independent magnetic susceptibility was found for LuV0.15 Ge2 in the high temperature region, whereas an anomaly was present at low temperatures. Highlights: Crystal structures and magnetic properties of new intermetallics studied. TmV0.17 Ge2 and LuV0.15 Ge2 crystallize in orthorhombic CeNiSi2 -type structure. Magnetic susceptibility of TmV0.17 Ge2 obeys Curie-Weiss law in paramagnetic region. LuV0.15 Ge2 is a Pauli paramagnet.